Mobility and the kinetic politics of migration and development. Issue 4 (12th February 2016) - Suliman, Samid
Abstract: The basic claim of this article is that when the 'migration-development nexus' is conceived through a 'mobilities' lens, a different account of politics is possible. I refer to this different account of politics as 'kinetic politics', to denote that polity formations and political relations are not spatially determined (that is, by processes of boundary formation and relations that travel across these boundaries), but are constituted through movement as people come and go. I argue for a methodological reorientation towards understanding the kinetic politics of development, in order to apprehend the ways in which migrants and migrancy are implicated in the constitution of the polities through which 'development' is organised. The recognition of movement as a transversal political relation that cuts across territorial boundaries has implications for the ways in which development is analysed and pursued. I propose that this line of inquiry opens up space to think critically about whether or not formal political membership will remain tethered to problematic territorial and technocratic approaches to 'sustainable' development. Might there be space for thinking about migrancy as the basis for rights, and political community as inherently kinetic?